List of Communications Received Relating to General Assembly Matters - Héderváry, Claire de (1958)
Records of this digital collection were assembled to document the work of the UN Special Committee on the Problem of Hungary established on January 10, 1957 by the United Nations General Assembly for the purpose of investigating the 1956 Hungarian revolution. Principal contributor(s): United Nations. General Assembly Communication to the General Assembly containing the names of 33 Hungarian newspapermen executed, condemned to death or imprisoned; request for the declaration of a day of mourning to commemorate the uprising and the execution of Imre Nagy and his associates; request for the release of Hungarian workers and writers imprisoned by the regime; protest against the imprisonment of minors for their participation in the revolution.